New Directions in the Use of Brain Stimulation Interventions in Patients with Obsessive-Compulsive Disorder - Dell'Osso, Bernardo; Cremaschi, Laura; Oldani, Lucio; Altamura, A. C. (Current Medicinal Chemistry, 2018)
Obsessive-Compulsive Disorder (OCD) is a highly disabling condition with early onset and chronic course in most of the affected patients. In addition, OCD may show high comorbidity and suicide attempt rates, which worsen the overall burden of the disease for patients and their caregivers. First-line treatments for OCD consist of pro-serotonergic compounds and cognitive-behavioral therapy. Nonetheless, many patients show only limited benefit from such interventions and require additional “next-step” interventions, including augmentative antipsychotics and glutamate-modulating agents. Based on the knowledge about altered neurocircuitry in OCD, brain stimulation techniques, including transcranial magnetic and electrical stimulations (TMS and tDCS) and deep brain stimulation (DBS), have been increasingly investigated over the last decade, revealing positive results for otherwise intractable and treatment-refractory patients. Available evidence in the field is in continuous evolution and professionals actively involved in the management of OCD patients, psychiatrists in particular, need to be updated about latest developments. Through the analysis of controlled studies, meta-analyses, and International treatment guidelines, the present article is aimed at providing the state of the art on the use of brain stimulation techniques for the treatment of OCD.
Keywords: Transcranial Magnetic Stimulation (TMS)